2009
DOI: 10.1080/13547500903067744
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of urinary biomarkers for early detection of acute kidney injury following cardiopulmonary bypass

Abstract: The purpose of this study was to compare the performance of six candidate urinary biomarkers, kidney injury molecule 1 (KIM-1), N-acetyl-β-(D)-glucosaminidase (NAG), neutrophil gelatinaseassociated lipocalin (NGAL), interleukin 18 (IL-18), cystatin C, and α-1 microglobulin, measured 2 hours following cardiopulmonary bypass (CPB) for the early detection of acute kidney injury (AKI) in a prospective cohort of patients undergoing cardiac surgery. 103 subjects were enrolled, AKI developed in 13%. Urinary KIM-1 ach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
162
0
13

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 221 publications
(185 citation statements)
references
References 38 publications
10
162
0
13
Order By: Relevance
“…The AUCs for KIM-1 to predict AKI at the time of ICU admission ranged between 0.57 and 0.78. [48][49][50] The predictive value of KIM-1 increased and reached an AUC of 0.83 at 12 hours postoperatively, a time point at which organ injury might be advanced and irreversible. 50 KIM-1 in CIN.…”
Section: Cysc In Acs and Congestive Hfmentioning
confidence: 99%
See 1 more Smart Citation
“…The AUCs for KIM-1 to predict AKI at the time of ICU admission ranged between 0.57 and 0.78. [48][49][50] The predictive value of KIM-1 increased and reached an AUC of 0.83 at 12 hours postoperatively, a time point at which organ injury might be advanced and irreversible. 50 KIM-1 in CIN.…”
Section: Cysc In Acs and Congestive Hfmentioning
confidence: 99%
“…In 3 studies 48,51,52 enrolling 258 patients undergoing cardiac surgery, urinary IL-18 showed a moderate predictive performance for AKI with an AUC ranging from 0.53 to 0.66 at postoperative ICU admission. Parikh and associates 51 concluded that the combination of urinary IL-18 with urinary NGAL may allow for the reliable early diagnosis and prognosis of AKI after CPB, much earlier than the rise in sCr.…”
Section: Il-18mentioning
confidence: 99%
“…Cardiac surgery has long been used to study AKI because of the ability to prospectively follow patients before and after a well timed renal insult; for this reason, several urinary proteins have been shown to serve as biomarkers of AKI after cardiac surgery, including neutrophil gelatinase-associated lipocalin (NGAL) (16)(17)(18)(19)(20), cystatin C (CyC) (19,21), kidney injury molecule-1 (KIM-1) (18,21), interleukin-18 (IL-18) (22), and ␣-glutathione-S-transferase (␣-GST) (23,24). Limited data are available comparing the ability of these markers to predict renal outcomes at the time of AKI diagnosis.…”
mentioning
confidence: 99%
“…Two other studies have found much greater sensitivity, of more than 90%, when KIM-1 is measured 2 and 6 h after cardiopulmonary bypass. However, it's sensitivity is decreased to 74% after 12 h cardiopulmonary bypass (34,35). Larger studies are needed to determine when is the optimal timing for determination and measurement of KIM-1 levels in relation to the exposure to etiological factors that may cause AKI.…”
Section: Discussionmentioning
confidence: 99%